The timing of smoking onset, prolonged abstinence, and relapse in men: A prospective study from ages 18 to 32 years - Kerr, David C. R. (2011)
AIM: To describe the rate and timing of smoking onset, prolonged abstinence (≥ 1 year), and relapses across ages 18 to 32 years in initially smoking and nonsmoking men. DESIGN: A 23-year longitudinal study. SETTING: Untreated community sample. PARTICIPANTS: 154 American boys were recruited at age 10 years to a larger study (n = 206) of delinquency risk; 71 participants who smoked cigarettes and did not use smokeless tobacco and 83 participants who did not use tobacco were followed from age 18 to 32 years. MEASUREMENTS: Frequency of tobacco use and weekly cigarettes smoked in the past year were assessed annually. Onset (> 6 cigarettes/week), abstinence (0 tobacco uses in the past year), and relapse (> 0 cigarettes/week) were tracked annually. FINDINGS: 36% of smokers achieved 1 or more years of abstinence by age 32 years. 52% who reached abstinence relapsed at least once. One half of men who showed onset after age 18 years were smoking at the end of study, compared to nearly three quarters of men who were smokers at age 18 years. Risk for relapse following prolonged abstinence was strongest initially and diminished thereafter. Transition probabilities were stronger for the second period of abstinence than for the first. Models were limited by sample size and statistical power. CONCLUSIONS: Relapses continue to erode men’s quit success even after long periods of abstinence from smoking. Long-term abstinence, despite intervening relapse, bodes well for eventual abstinence. Adolescent onset appears relevant to the likelihood of adult abstinence and relapse patterns.